Delta globin gene variations leading to reduction in HbA2 levels. (27th July 2016) - Hariharan, P.; Colaco, S.; Colah, R.; Ghosh, K.; Nadkarni, A.
Summary: Introduction: Mutations in the δ‐globin gene are not pathogenically relevant, but co‐inheritance of δ‐globin variants along with β‐globin gene defects can mask the diagnosis of β‐thalassaemia trait. Methods: Routine haematological parameters were carried out. Molecular analysis of β‐globin gene mutations was carried out by CRDB, ARMS and DNA sequencing. δ‐ globin gene analysis was carried out by DNA sequencing. Results: In this case study, we report a β−thalassaemia trait (IVS 1‐5G→C) (HBB:c.92 + 5G→C) with HbA2 of 1% showing the presence of δ‐globin gene variant HbA2 St. George CD 81 (C→T) (HBD:c.244C→T). A similar observation was reported in another unrelated patient who showed near absence of HbA2 level in HPLC. He showed a presence of δ‐globin gene mutation HbA2 Saurashtra CD 100(C→T) (HBD: c.301C→T) and a single 3.7 kb deletion in the α‐globin gene. Conclusion: In the countries, where β‐thalassaemia is prevalent, an awareness and detection of different δ‐globin gene mutations is important, as complex interactions between these haemoglobinopathies can lead to the misdiagnosis of β‐thalassaemia carriers.